Enhancing Students’ Future Thinking Skills on Deforestation Through the Know, Understand, Do (KUD) Strategy: A Quasi-Experimental Study - Ana Nurul Auliah; Suhendar; Gina Nuranti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
Future thinking skills are essential for preparing students to face complex global challenges through imaginative, strategic, and anticipatory thinking. However, empirical research on these skills is still limited, especially at the high school level. Based on observations, students' future thinking skills at SMAN X Sukabumi City are still low because learning does not encourage future thinking. This study aims to examine the effect of the Know, Understand, Do (KUD) strategy on students’ future thinking skills, analyze skill levels across specific indicators and gender, and explore students’ responses to the learning. Using a quasi-experimental design with a non-equivalent control group, data were collected through validated essay tests and student response questionnaires. Results indicate that the KUD strategy significantly improves students’ future thinking skills (p = 0.018), with higher normalized gain scores (N-Gain = 0.70) compared to the control group (N-Gain = 0.59). Analysis of indicators shows notable improvements in visioning, predicting, planning, anticipating, and evaluating. Gender differences did not significantly affect outcomes. Additionally, student responses revealed a high level of engagement and perceived relevance of the strategy. These findings highlight KUD as a promising strategy to foster anticipatory and sustainable thinking among students.